2008
DOI: 10.1002/ejic.200800831
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Solvent‐Induced Spontaneous Homochiral Assembly of Bidentate Bis(N,N′‐diaryl‐N‐heterocyclic carbene)‐Palladium Complexes

Abstract: A series of new bidentate bis(N‐heterocyclic carbene)‐palladium complexes 4a–e and 6 with xanthene framework was synthesized. The X‐ray analyses of the complexes revealed that the complexes have conformational chirality. Homochiral crystals of 4a and 6 were obtained by recrystallization from THF or 1,4‐dioxane as solvent. The energy barriers for racemization of the complexes were calculated from dynamic NMR spectroscopy. (© Wiley‐VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2008)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Spectroscopic characterizations identical to literature. 17 N- 3). Compound 2 (16.00 g, 29.93 mmol, 1.0 eq.)…”
Section: Synthesismentioning
confidence: 99%
“…Spectroscopic characterizations identical to literature. 17 N- 3). Compound 2 (16.00 g, 29.93 mmol, 1.0 eq.)…”
Section: Synthesismentioning
confidence: 99%
“…The isolation and crystallographic characterization of thermally stable N-heterocyclic carbenes (NHCs) by Arduengo et al initiated a considerable amount of research into the organometallic chemistry of these versatile ligands. Since this discovery, a wide range of different NHC ligands have been prepared, including systems which incorporate NHCs in chelate and pincer scaffolds. It has been shown that these ligands coordinate to most transition metals and can be utilized in a number of important catalytic reactions, particularly using Pd. , Surprisingly, given the plethora of research into bidentate chelating NHC ligands for Pd, only a handful are known to coordinate in a trans fashion (NHC−M−NHC close to 180°). Selected examples are shown in Figure . The first example ( i ) was described in 2000 by RajanBabu et al and contains two dinapthyl groups .…”
Section: Introductionmentioning
confidence: 99%
“…However, only two examples of N ‐Mes, N ′‐Dipp imidazolium salts were described. Since that time, surprisingly a few examples of unequally 1,3‐diaryl‐substituted imidazolium salts have been synthesized by this method and utilized for the preparation of the corresponding metal complexes . In the present work, we for the first time investigated the reaction of the binucleophilic fluorinated arylamine 3 with the mesityl‐substituted oxazolinium salt 4 and synthesized a new type of functionalized NHC precursors.…”
Section: Resultsmentioning
confidence: 99%